2016
DOI: 10.1177/1359105316669859
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese validation of the Short Health Anxiety Inventory: Factor structure, reliability, and factor invariance

Abstract: The Short Health Anxiety Inventory is a brief instrument to assess health anxiety widely used across countries; however, no validated version is available for Portuguese-speaking population. Factorial structure, reliability, and equivalency factor with the Spanish version were analyzed with Portuguese adolescents aged 14-18 years. A Portuguese adolescent cohort ( N = 629) and a comparative Spanish adolescent cohort ( N = 1502) were evaluated. The original two-factor version was the best fitting model for the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
11
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 32 publications
4
11
1
Order By: Relevance
“…Overall, our findings suggest good internal consistency of the Spanish version of the SHAI. The internal consistency of the SHAI total scale was similar to what was found in other studies (Morales et al, 2016), although some studies have reported slightly higher internal consistency ( α range: .91-.96) (Abramowitz, Olatunji et al, 2007; Kocjan, 2016). Furthermore, the Illness likelihood subscale demonstrated adequate internal consistency, whereas the Negative consequences of illness subscale only showed acceptable internal consistency.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Overall, our findings suggest good internal consistency of the Spanish version of the SHAI. The internal consistency of the SHAI total scale was similar to what was found in other studies (Morales et al, 2016), although some studies have reported slightly higher internal consistency ( α range: .91-.96) (Abramowitz, Olatunji et al, 2007; Kocjan, 2016). Furthermore, the Illness likelihood subscale demonstrated adequate internal consistency, whereas the Negative consequences of illness subscale only showed acceptable internal consistency.…”
Section: Discussionsupporting
confidence: 86%
“…Since its development and publication, the SHAI has been widely used to assess health anxiety, and several studies in different countries have supported its reliability and validity in both clinical and non-clinical samples (see Alberts, Hadjistavropoulos, Jones, & Sharpe, 2013 for a review). For example, the SHAI internal consistency ranged from α =.82 (Morales, Reis, Espada, & Orgilés, 2016) to α =.96 (Abramowitz, Olatunji, & Deacon, 2007), and test-retest reliability ranged from r = .56 (Zhang, Liu, Li, Mao, & Yuan, 2015) to r = .90 (Salkovskis et al, 2002). Moreover, the questionnaire showed high associations with hypochondriacal symptoms, but the associations were only moderate with worry, anxiety sensitivity, obsessive-compulsive, or depressive symptoms (Abramowitz et al, 2007, Abramowitz et al, 2007, Wheaton et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…and most validations of the SHAI" (Arnáez et al, 2019, p. 255). In contrast, Morales et al (2018) found that the three-factor model did not fit the data well, whereas the original two-factor did.…”
mentioning
confidence: 75%
“…Third, the SHAI has been adapted and validated in various cultures and languages, including Portuguese (Morales et al, 2018), Turkish (Aydemir et al, 2013), German (Bailer et al, 2013), Spanish for both adolescents (Morales et al, 2015) and adults (Arnáez et al, 2019), Chinese (Zhang et al, 2015), Polish (Kocjan, 2016), Persian (Mehdi et al, 2013), North American (Abramowitz, Deacon, & Valentiner, 2007), and Dutch (Te Poel et al, 2017). This adaptation facilitates cross-cultural comparisons and permits extending psychological science beyond particular cultural backgrounds, especially if the latent scale structure was found invariant across targeted cultures.…”
mentioning
confidence: 99%